Biosorption of copper (II) from aqueous solution by using dried water hyacinth (Eicchornia Crassipes) - Nur Suhada, Sulaiman (2009)
This paper presents the results of research on capability of water hyacinth (Eichhornia crassipes) as low cost biosorbent in removing Cu (II) from aqueous solution and to identify the optimum uptake of Cu (II) based on four parameters that are effect of adsorbent dosage, initial concentration, pH and time contact by biosorption which could be used as an alternative approach to remove Cu (II) from water or selected wastewater. A series of batch studies were conducted using different amount of water hyacinth (0.1 - 0.6 g), different concentration of Cu (II) solution range from 10 to 100 mg/L at various pH values and time, shaken with constant stirring speed of 120 rpm at room temperature. It was found that Cu (II) has removed about 58 % at 0.5 grams of water hyacinth and the optimum initial concentration is at 80 mg/L with removal of 64 %. The biosorption of Cu (II) is found occurred at acidic (62 %) as the availability of negatively charged groups at the biosorbent surface which is necessary for the sorption of metals to proceed and copper was highly removed at 40 min due to surface adsorption on the biomass. The experimental has proved that water hyacinth are capable in removing Cu (II) and good biosorbent as it is low cost and indirectly solved environmental problem made from this easily growth plants and biosorption is an efficient technology replacing other conventional method in treating the wastewater.